Hereditary spherocytosis due to a novel variant, p.Q1034X, in the beta subunit of the spectrin gene: A case report - Emmalee M. Kugler; Akash Patel; Faraz Afridi; Maria I. Scarano; Rafat Ahmed (Elsevier, 2024)
Background: Heterozygous pathogenic variants of SPTB cause hereditary spherocytosis (HS) in a quarter of cases. Case report: A 14-day-old male presenting with persistent anemia and hyperbilirubinemia was diagnosed with HS by increased red blood cell osmotic fragility and decreased fluorescence on the eosin-5'-maleimide binding test. For his failure to thrive and hypotonia, genetic sequencing revealed a de novo variant of the SPTB gene (p.Q1034X) on exon 15. This variant is predicted to cause loss of normal protein function either through protein truncation or nonsense-mediated mRNA decay. A variant of uncertain significance (p.R438W) in the chondroitin sulfate synthase 1 (CHSY1) gene was incidentally found. Loss of CHSY1 is associated with autosomal recessive Temtamy preaxial brachydactyly syndrome (TPBS). However, this patient's heterozygosity and lack of typical TPBS phenotype make this variant less likely the cause of his symptoms. Conclusion: Further investigation can evaluate a potential link between the patient's presentation and these gene variants.